Institutional change and FDI in three selected CEECs: The Czech Republic, Hungary and Poland - Maria Grazia Attinasi; Nicola Melloni; Anna Soci (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
The European enlargement provides new space for re-organizing the production and re-locating the plants. Few studies approach the complex theme of industrial location in the EU new-comers: statistics are still scarce, language constitutes a barrier for assuming reliable information, and the differences in the economic and institutional structure bring further difficulties. This paper aims at investigating the relation between institutional change in this area and FDI. In particular, the focus will be on the privatisation process, which has played a major role in determining the behaviour of the firms and thus the direction of the FDI.
Keywords: 330